ONOMATOPE DALAM NOVEL MANUSIA SETENGAH SALMON KARYA RADITYA DIKA - Ela Karlinda; M. Nur Mustafa; Mangatur Sinaga (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: Basically, the study aims to describe the type, word class, and structure of onomatopeia in the novel Manusia Setengah Salmon by Raditya Dika. Type of this study is qualitative study and explain the result study according to descriptive. The result of study and discussion of data acquisition, there are four types onomatopeia in the novel Manusia Setengah Salmon by Raditya Dika that is (1) onomatopeia of the human, (2) onomatopeia of the animal, (3) onomatopeia of the object, (4) onomatopeia of the everyday life. Word class onomatopeia in the novel Manusia Setengah Salmon by Raditya Dika that is (1) verb class, (2) noun class, (3) adjective class, (4) adverb class, (5) assignment class. Structure onomatopeia in the novel Manusia Setengah Salmon by Raditya Dika that is (1) monosyllables, (2) bisyllables, and (3) multisyllables.Key Words: Onomatopeia, novel, manusia setengah salmon